The Impact of Trade Facilitation on Cross-Border E-commerce Trade: Evidence from China - Chenggang Wang; Tiansen Liu; Yue Zhu; Meng Lin; He Wang; Hanchen Li (SAGE Open)
With the rapid expansion and growing influence of global cross-border e-commerce trade, the significance of trade facilitation in this context has become increasingly evident. To comprehensively examine the specific pathways through which trade facilitation impacts cross-border e-commerce trade, this paper focuses on the cross-border e-commerce trade activities within China’s cross-border e-commerce trade comprehensive experimental zone. We employ the differences-in-differences method to analyze pertinent issues. The explanatory variables consist of the effects of trade facilitation policies, while the mediating variables encompass information technology capability and economic scale. The conclusions of this paper are as follows: (1) The implementation of trade facilitation measures within the cross-border e-commerce comprehensive experimental zone has been found to enhance the sustainability of cross-border e-commerce trade. (2) The development of information technology capabilities has proven to be beneficial for the growth of cross-border e-commerce trade. (3) Trade facilitation measures show a more pronounced impact on promoting cross-border e-commerce trade in regions with higher levels of economic development. Conversely, regions with lower levels of economic development exhibit a relatively weaker influence of trade facilitation on cross-border e-commerce trade. The conclusions are expected to offer valuable insights and guidance for governmental authorities and enterprises involved in cross-border e-commerce trade when making informed management decisions.